A critical analysis on the adequacy of the legal framework in providing education to refugee children in Malaysia / Nor Azean Mohd Sohaini, Norhamizah Kamarudin and Umar Faiz Abdul Kohar - Mohd Sohaini, Nor Azean; Kamarudin, Norhamizah; Abdul Kohar, Umar Faiz (2011)
This research is to determine whether the current legal framework is adequate in providing education to the refugee children in Malaysia. There are two main objectives of the study, firstly, to examine whether or not the current legal framework is adequate in providing education to the refugee children in Malaysia. The second objective is to recommend any viable alternative to the current legal framework in providing better education to refugee children in Malaysia. In conducting this research, semi-structured interviews, library based research and internet based research will be conducted for the purposes of collecting the information regarding the rights to education for refugee children. For the purpose of answering the research question, relevant domestic laws have been examined in order to determine whether refUgee children can have access to education in Malaysia. International instruments such as Convention on the Rights of the Child (CRC), Universal Declaration of Human Rights (UDHR), International Covenant on Civil and Political Rights (ICCPR), International Covenant of Economic, Social and Cultural Rights (ICESCR) have also been examined in order to ensure whether Malaysia meets the international standards. This research paper concludes that domestic law in Malaysia is not adequate in providing access to education to refugee and Malaysia should take steps to withdraw the reservation expressed to CRC.